THE POTENTIAL DEVELOPMENT STRATEGY OF PESANTREN LITERATURE TO SUPPORT A RELIGIOUS TOURISM TOWARDS A CREATIVE INDUSTRY - Faridi, Abdurrachman (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2011)
PesantrenÃ¢â¬â¢s literature is a cultural treasure which exists in Indonesia. PesantrenÃ¢â¬â¢s enchantment can be viewed from many sides; i.e. environment, education, teaching, human, even customs and arts. These conditions provide a variety of potential to be optimized. The aim of this study is to expose the potential and model of pesantrenÃ¢â¬â¢s literature to support religious tourism as a creative industry. The result of this study is to optimize the potential development strategy of pesantrenÃ¢â¬â¢s literature and to support religious tourism as a creative industry. PesantrenÃ¢â¬â¢s literature is used as one of religious tourism attractions that brings the economic life towards a creative industry, and to create other economic activities beneficial for the grassrootsÃ¢â¬â¢ level. ÃÂ Keywords: pesantrenÃ¢â¬â¢s literature, religious tourism, creative industry